New hashing-based multiple string pattern matching algorithms - Khancome, Chouvalit; Boonjing, Veera (My University, 2012)
The paper presents three new algorithms for multiple string pattern matching using hashing tables: a suffix search (SS), a suffix-prefix search (SPS), and a suffix-middle-prefix search (SMPS). It takes O(|P|) time and space preprocessing where |P| is the sum of all pattern lengths. They search for a fixed-length pattern m in a text with length |t| takes O(|t| |P|) in the worst case, O(|t|) in an average case, and O(|t|/m) in the best case. Furthermore, their attempting times are less than of traditional algorithms. © 2012 IEEE.
Keywords: Matching Algorithm; Multiple String Pattern Matching; Static Dictionary Matching; String Matching